POSITIVE REINFORCEMENT STRATEGIES: BOOSTING STUDENTS’ ACHIEVEMENT - Zahroh, Alfin Amaliah; Yeni Prastiwi; Nur Hidayat (JPGENUS: Jurnal Pendidikan Generasi Nusantara, 2025)
Positive reinforcement, which involves acknowledging and rewarding desirable behaviors, is widely recognized as an effective tool in promoting a conducive learning environment. The study aims to investigate the correlation between reinforcement methods, such as praise, rewards, and recognition, and their effects on students' academic performance, and overall engagement to vocational school students. Using a quantitative method approach, data was collected from a sample of vocational school students through survey. Quantitative measures assessed student performance before and after the application of positive reinforcement strategies.  Key variables analyzed include frequency and type of reinforcement, student self-efficacy, participation levels, and achievement in core subjects.